PROFILE OF MEDICOLEGAL AUTOPSIES CONDUCTED AT A TERTIARY CARE CENTRE IN INDORE (M.P.) (Journal of Forensic Medicine & Toxicology, 2020)
Death is an inevitable aspect which can be due to both natural and unnatural causes. Profiling of autopsies is necessary in order to prevent the unnatural deaths in future by understanding the pattern of unnatural deaths in the society. It also helps in improving the healthcare system and also reflects flaws and drawbacks prevailing in the society. The present study was based on retrospective analysis of the autopsies performed during the period from January 2018 to December 2018 in the Department of Forensic Medicine and Toxicology, MGM Medical College, Indore (M.P). A total of 2447 cases were brought for post-mortem examination of which, majority of victims were males 1826 (74.6%) cases. Maximum number of cases i.e. 690 (28.2%), belonged to the age group of 21–30 years. Natural death accounted for 405 (16%) cases and unnatural death 1951(80%) cases. Among unnatural deaths major cause of death were road traffic accident (RTA) in 1040 (42.5%) cases, followed by Asphyxial deaths
Keywords: RTA; Asphyxia; Poisoning; Natural Deaths; Unnatural Deaths.